Splicing of phenylalanine hydroxylase (PAH) exon 11 is vulnerable: molecular pathology of mutations in PAH exon 11 - Heintz, Caroline; Blau, Nenad (Molecular genetics and metabolism, 2012)
In about 20-30% of phenylketonuria (PKU) patients, phenylalanine (Phe) levels can be controlled by cofactor 6R-tetrahydrobiopterin (BH4) administration. The phenylalanine hydroxylase (PAH) genotype has a predictive value concerning BH4-response and therefore a correct assessment of the mutation molecular pathology is important. Mutations that disturb the splicing of exons (e.g. interplay between splice site strength and regulatory sequences like exon splicing enhancers (ESEs)/exon splicing silencers (ESSs)) may cause different severity of PKU. In this study, we identified PAH exon 11 as a vulnerable exon and used patient derived lymphoblast cell lines and PAH minigenes to study the molecular defect that impacted pre-mRNA processing. We showed that the c.1144T>C and c.1066-3C>T mutations cause exon 11 skipping, while the c.1139C>T mutation is neutral or slightly beneficial. The c.1144T>C mutation resides in a putative splicing enhancer motif and binding by splicing factors SF2/ASF, SRp20 and SRp40 is disturbed. Additional mutations in potential splicing factor binding sites contributed to elucidate the pathogenesis of mutations in PAH exon 11. We suggest that PAH exon 11 is vulnerable due to a weak 3′ splice site and that this makes exon 11 inclusion dependent on an ESE spanning position c.1144. Importantly, this implies that other mutations in exon 11 may affect splicing, since splicing is often determined by a fine balance between several positive and negative splicing regulatory elements distributed throughout the exon. Finally, we identified a pseudoexon in intron 11, which would have pathogenic consequences if activated by mutations or improved splicing conditions. Exonic mutations that disrupt splicing are unlikely to facilitate response to BH4 and may lead to inconsistent genotype-phenotype correlations. Therefore, recognizing such mutations enhances our ability to predict the BH4-response.
Gesehen am 20.04.2018